Balancing Stability and Agility: the Role Software Ecosystems in Enhancing Public Service Delivery in the Public Sector - Kolehmainen, Taija (2024)
This is an article-based Master's thesis that explores how software ecosystems, integrating public and private partners, improve public service delivery by balancing stability and agility. Public sector organizations face increasing pressure to be adaptive and resilient, particularly during crises like the COVID-19 pandemic, which exposed the limitations of traditional rigid and hierarchical models of service delivery. The research focuses on answering the central question: "How do software ecosystems improve public service delivery in the public sector while balancing the need for stability and agility?" The study employs a qualitative analysis of the findings of two primary articles: one on Finland's Omaolo e-health service, which demonstrated rapid adaptation during the pandemic, and another on the role of Enterprise Architecture in government ecosystems. Insights were gathered from literature and primary studies, analyzing how leadership, governance, and collaboration contribute to system agility and stability. Key findings reveal that software ecosystems enhance public service efficiency by pooling resources, fostering innovation, and promoting adaptability. The study highlights the role of governance structures like Enterprise Architecture in maintaining stability while enabling flexibility. Clear communication, strong public-private collaboration, and adaptive leadership are key to balancing agility and stability. Continuous improvement and reconfigurable processes ensure both responsiveness and long-term resilience in public service delivery. The study concludes that public sector organizations can significantly improve service delivery by adopting software ecosystems that integrate both stability and agility. In this study, I discovered that public organizations can adopt agility more effectively than previously thought, particularly in crisis situations. Enterprise Architecture does not only support stability but also enhances agility by allowing flexible system reconfiguration. More research is needed to explore how measures implemented during crises can be institutionalized into long-term governance models. Additionally, further investigation is needed into leadership styles and organizational culture shifts that best facilitate continuous improvement and innovation in public sector ecosystems.